GAMBARAN PERAN STRUKTURAL KELUARGA PADA REMAJA SELAMA MASA PANDEMI COVID-19 - Prabarini, Lintang Puspita; Jainurakhma, Janes (Coping: Community of Publishing in Nursing; Vol 11 No 2 (2023): April 2023, 2023)
The psychosocial development of adolescents during the COVID-19 pandemic was disrupted. Restrictions on social interaction due to the lockdown have an impact on adolescent developmental tasks, which are dominant and only take place in the family environment. The purpose of this study was to describe the role of the family structurally on adolescent welfare. This study used a descriptive observative method, sampling was carried out by screened sampling. The results showed 82,2% of the level of influence of internal factors on family roles in this study was moderate, describing family conditions, in the form of family composition , the influence of gender on beliefs and care roles; high external elements of 54,3% describe the influence of the extended family, and family social contact, with the environment; and family contextual factors in this study were moderate (59,7%) which described ethnicity, cultural influences, social class, religion, and beliefs. Lockdown rules during the pandemic made teenagers spend more time at home than socializing with peers. Support and the role of the family play an important role in the health and developmental tasks of the family during the COVID-19 pandemic.